The Effect of Pharmaceutical Care Practices on Clinical Problem-Solving Decision-Making Competencies and Students’ Preparedness: A Cross Sectional Study - Yürük, Fatima Ulya; Mercanoğlu, Güldem; Yüksel, Gülrû; Ay, Zeynep Yeşim; Uçar, Nazlıcan; Tezcan, Songül (Indian Journal of Pharmaceutical Education and Research, 2025)
Background As clinical responsibilities continue to grow, it becomes essential for clinical pharmacists to acquire advanced competences, such as patient monitoring, patient-specific drug therapy design and evaluation, and collaboration with healthcare professionals. Pharmacy schools aspire to equip young pharmacists with competencies relevant to their current needs through the clinical practice courses they offer. Therefore, investigating the impact of clinical practice from the students’ perspectives is crucial. Aim The study aims to explore the influence of experiential learning provided in Pharmaceutical Care (PC) courses on students’ level of perceived professional readiness, clinical problem-solving, reasoning, and decision-making skills. Materials and Methods This study is a cross-sectional survey. Data were collected from a total of 278 students of PC courses using two questionnaires: Perceptions of Preparedness to Provide Pharmaceutical Care (PREP) scale and the Clinical Pharmacist Competencies Self-Evaluation Questionnaire (CPCSE). Results The reliability coefficients of the PREP and CPCSE questionnaires were calculated as 0.95 and 0.98, respectively. There was a statistically significant difference between the semesters in the students’ readiness perceptions, and the students’ perceptions were at the highest level at the end of the PC practices (p <0.00). A statistically significant linear relationship was found between the students’ perception of readiness at the end of the 9th semester and their problem-solving and decision-making competencies (r = 0.534 p<0.000). Conclusion The results of the study highlight possible areas for curricular improvement. Given that the students deemed themselves to be least prepared for the administrative procedures, the curriculum should be reconsidered in this respect. The findings derived from the competency survey further underscore the necessity for curriculum modifications about drug administration and collaboration.
Keywords: Clinical pharmacist competency; Experiential learning; Pharmacy education; Clinical pharmacy; Pharmaceutical care